Qualidade do sêmen de carneiros Santa Inês baseada em índices bioclimáticos e avaliação de protocolos de congelação - Molina, Júlio Constantino Jerí (2021)
The quality of ram semen in tropical countries is threatened by environmental stress and sperm damage from freezing, leading to the need for greater knowledge of the effect of the environment on reproductive aspects and improvement of cryopreservation protocols. In this sense, the aim of this study was i) to identify the best time of year to collect fresh semen and ii) to determine the effect of the interaction between extenders and freezing rates on the quality of frozen-thawed ram semen. The relationships between bioclimatic indices that measure heat stress and the reproductive parameters (RP) of Santa Inês rams (n = 25) raised in the Northeast region of Brazil were studied. The indices of Temperature and Humidity (THI), Equivalent Temperature (ETI), Black Globe Temperature and Humidity (BGTHI), and Thermal Comfort (TCI) were calculated considering the previous period of spermatogenesis (P45) and period of sperm transit through the epididymis (P15) in the first (Q1), second (Q2), and third (Q3) four-month period of the year. RP analyses were performed using the mixed model, and their variation between four-month periods was determined by the Tukey/Dunn test. The sperm kinetic RP in Q1 were worse than in Q2 and Q3 (p < 0.05). All indices evaluated showed an antagonistic relationship with most RP. The BGTHI and TCI showed a negative relationship with the curvilinear, straight line, and average path velocities (VCL, VSL, and VAP) and a positive relationship with slow spermatozoa in P45 and P15. The BGTHI and TCI classified the environment more consistently with the response of sperm kinetics, which were affected when the index was above 83 in P45 and above 41 in P15; these levels are considered dangerous and uncomfortable for sheep. We also evaluated the effects of the interaction between four extenders (Factor 1), with a base of soybean lecithin (0.5, 1.0, and 2.0 %) and 20% egg yolk (control), and three freezing rates (Factor 2), of 10, 20, and 60 °C/min, on the sperm parameters (SP) in the thawed semen of Santa Inês rams (36 pools of ejaculates from 12 rams). The effects of the factors and their interactions were analyzed by ANOVA following a 4 × 3 factorial design, and by the F Test. The differences between the experimental groups were determined by the Tukey Test. The analyses of computerized sperm kinetics, flow cytometry, and fluorescence techniques allowed semen samples from the 20% egg yolk and the 60 °C/min interaction to be identified as having higher percentages of sperm with better kinetic parameters that were non-apoptotic with intact membrane, were noncapacitated, and were smaller with acrosome reaction, showing that this interaction better protects sperm in the frozen ram semen. Based on the results of the study, strategies can be used to improve the quality of fresh semen, collecting it between the second and third fourmonth period of the year. Additionally, use of a 20%-egg-yolk-based e